2015
DOI: 10.1007/s13204-015-0428-4
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis, characterization and antimicrobial studies of green synthesized silver nanoparticles from fruit extract of Syzygium alternifolium (Wt.) Walp. an endemic, endangered medicinal tree taxon

Abstract: In nanotechnology, the plant mediated synthesis of nanoparticles has terrific application in biomedicine due to its novel properties and its eco-friendly nature. The present study deals with the biosynthesis of stable silver nanoparticles (SNPs) from aqueous fruit extract of S. alternifolium an endemic medicinal plant to Eastern Ghats. The synthesized nanoparticles are characterized by UV-VIS spectroscopy, FTIR, XRD, AFM, SEM with EDAX and TEM. Colour change from brown to grey indicates the formation of nanopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
24
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 24 publications
9
24
0
1
Order By: Relevance
“…It is observed that reflections are sharp and high in intensity, indicating that the prepared silver nanoparticles are highly crystalline in nature. Similar results were found by Yugandhar et al [41] using Syzygium alternifolium stem extracts mediated synthesis of silver nanoparticles.…”
Section: X-ray Diffraction (Xrd)supporting
confidence: 89%
See 1 more Smart Citation
“…It is observed that reflections are sharp and high in intensity, indicating that the prepared silver nanoparticles are highly crystalline in nature. Similar results were found by Yugandhar et al [41] using Syzygium alternifolium stem extracts mediated synthesis of silver nanoparticles.…”
Section: X-ray Diffraction (Xrd)supporting
confidence: 89%
“…However, the overuse of silver agents has decreased their efficiency as antimicrobial agent [41]. The results of present investigation revealed a considerable antibacterial activity of synthesized silver nanoparticles for all bacteria.…”
Section: Antibacterial Activitymentioning
confidence: 63%
“…In our previous studies, synthesis of silver nanopatricles from fruit extract of S. alternifolium shows spherical shaped nanoparticles with the size up to 68 nm [40]. In this study, the nanoparticles are spherical in shape having size range up to 44 nm.…”
Section: Resultssupporting
confidence: 47%
“…Overall, the rapid reduction of silver ions might be linked with the presence of water-soluble phytochemicals such as flavones, quinones, and organic acids present in the leaf extract of A. cymosa. AFM is a primary tool for analyzing size, shape, and agglomeration pattern [33]. It offers visualizations of three-dimensional views of the nanoparticles unlike the electron microscopes.…”
Section: Resultsmentioning
confidence: 99%